2013
DOI: 10.2478/aoas-2013-0010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of isoflavones on testicular weight and testosterone secretion in ISA Brown roosters

Abstract: Isoflavones are phytoestrogens which have estrogen-like activity in animals and humans. Because of this characteristic influence, the aim of this investigation was to examine the effect of genistein and daidzein on testicular weight and testosterone secretion in ISA Brown roosters. Genistein and daidzein as non-steroid phytoestrogens were added in large amounts to the feed of roosters. Soy isoflavones were added to rooster diets in amounts of 0, 300, 600, 1200 and 1800 mg/kg of feed. At the end of the 37th wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Isoflavones are well known to exert several oestrogen-like biological effects on animals because of the similarity of their structure to the natural oestrogen structure (Gjorgovska & Filev, 2013). In mammals, many studies have shown that isoflavones have a broad range of regulatory effects, such as antitumour effects, antioxidant effects and immune system regulation (Masilamani, Wei, & Sampson, 2012).…”
mentioning
confidence: 99%
“…Isoflavones are well known to exert several oestrogen-like biological effects on animals because of the similarity of their structure to the natural oestrogen structure (Gjorgovska & Filev, 2013). In mammals, many studies have shown that isoflavones have a broad range of regulatory effects, such as antitumour effects, antioxidant effects and immune system regulation (Masilamani, Wei, & Sampson, 2012).…”
mentioning
confidence: 99%
“…In our study we did not observe any changes in testosterone concentration as a result of SI supplementation. Other studies also reported no effects of SI on testosterone concentrations in roosters (Gjorgovska and Filev 2013) and rabbits (Yousef et al 2003;Yousef et al 2004). A seasonal variation in reproductive performance can be observed in goats, which accompanied the changes in hormone secretion.…”
Section: Discussionmentioning
confidence: 91%